1998
DOI: 10.1046/j.1464-410x.1998.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

An Italian epidemiological multicentre study of nocturnal enuresis

Abstract: Objective To estimate the prevalence of enuresis in schoolchildren in Italy. Subjects and methods The Italian Club of Nocturnal Enuresis promoted a prevalence study of nocturnal enuresis using a self‐administered questionnaire in seven cities in Northern, Central and Southern Italy. The association between enuresis and potential risk factors, e.g. a family history of enuresis, stress, socio‐economic status and abnormal diurnal voiding habits, was investigated. The perceived impact on the child and on the famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
94
6
14

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 5 publications
17
94
6
14
Order By: Relevance
“…A similar value has been reported in children in eastern countries [2]. In Italy a multicentre epidemiological survey, which recruited 9086 schoolchildren aged 6-14 years, found an overall incidence of NE of 3.8%, which progressively decreased from 8.1% and 9.6% at 6 years old, in males and females respectively, to 1.2% at 13 years old [3]. Bedwetting was more frequent in boys than in girls.…”
Section: Introductionsupporting
confidence: 81%
“…A similar value has been reported in children in eastern countries [2]. In Italy a multicentre epidemiological survey, which recruited 9086 schoolchildren aged 6-14 years, found an overall incidence of NE of 3.8%, which progressively decreased from 8.1% and 9.6% at 6 years old, in males and females respectively, to 1.2% at 13 years old [3]. Bedwetting was more frequent in boys than in girls.…”
Section: Introductionsupporting
confidence: 81%
“…Just one, Italian, study on enuresis was identified by the literature review, demonstrating an increased prevalence among families of low economic levels, irrespective of the age of the child. 20 Our results suggest that poorer children require special attention because of the greater frequency of symptoms.…”
Section: Discussionmentioning
confidence: 65%
“…Sıklığı toplumlara göre değişmekle birlikte, genel olarak 5 yaş civarında %15-%20, 10 yaşında %7, 12 yaşında %3 ve 15 yaşından sonra %1 olduğu kabul edilir (7,8). Enürezis noktürna fizyopatolojisinde klasik olarak üç faktör rol oynar: Uyanma bozukluğu, gece mesane kapasitesinin azalması ve gece idrar miktarının artması (noktürnal poliüri).…”
Section: Discussionunclassified